Role of Lactulose Rhamnose Permeability Test in Assessing Small Bowel Mucosal Damage in Children with Celiac Disease. (November 2020) - Khan, Muhammad Rehan; Faubion, William A.; Dyer, Roy; Singh, Ravinder; Larson, Joseph J.; Absah, Imad
Increased gut permeability has been suggested in patients with celiac disease (CD). We aimed to compare gut permeability in children using the lactulose/rhamnose permeability test. We prospectively recruited 55 children into 3 groups; 27 in group 1 (children with newly diagnosed celiac disease, 12 in group 2 (siblings of children with celiac disease) and 16 in group 3 (control group). The median age of participants was 11 years 2 months in group 1, 9 years 5 months in group 2 and 10 years 3 months in group 3. Standardized median delta rhamnose was lower in CD group as compared to control group (147.5 vs 3153.1, P  = 0.040). The low median rhamnose absorption in children with celiac disease as compared to other groups suggests that this test can differentiate between damaged and healthy mucosa, hence can it potentially can be used as a noninvasive test of mucosal healing in children with celiac disease.